1999
DOI: 10.1101/gr.9.6.558
|View full text |Cite
|
Sign up to set email alerts
|

A View of Modern Human Origins from Y Chromosome Microsatellite Variation

Abstract: The idea that all modern humans share a recent (within the last 150,000 years) African origin has been proposed and supported on the basis of three observations. Most genetic loci examined to date have (1) shown greater diversity in African populations than in others, (2) placed the first branch between African and all non-African populations in phylogenetic trees, and (3) indicated recent dates for either the molecular coalescence (with the exception of some autosomal and X-chromosomal loci) or for the time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…When using a combined African population and a number of non-African populations, a phylogenetic tree (arising from Y-chromosomal microsatellites) has its root located between Africans and non-Africans (Seielstad et al, 1999), hence Table 1 and Figure 5C and 5D may be surprising. Nevertheless, studies are congruent with there being migration back into Africa (e.g., Henn, Botigué et al, 2012; Hodgson et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…When using a combined African population and a number of non-African populations, a phylogenetic tree (arising from Y-chromosomal microsatellites) has its root located between Africans and non-Africans (Seielstad et al, 1999), hence Table 1 and Figure 5C and 5D may be surprising. Nevertheless, studies are congruent with there being migration back into Africa (e.g., Henn, Botigué et al, 2012; Hodgson et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, despite Y-chromosomal microsatellite heterozygosity being related to geographical distance from Africa (Balloux et al, 2009), that type of diversity was not indicated to signal the expansion. Yet that diversity was from six Y-chromosomal microsatellites (Balloux et al, 2009), i.e., not many (given Seielstad et al, 1999), so it really is not clear if the signal is present in the heterozygosity of Y-chromosomal microsatellites. As for where in Africa the expansion originated, the location of a geographical centroid (determined through a number of expansion indicators) and locations of peak points (using populations worldwide) adds weight to southern Africa being the origin (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations